RELEVANSI FILSAFAT PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMK PUSAT KEUNGGULAN - Jasman, Indra; Sadat, Anwar; Fransiska, Yulia; Jalinus, Nizwardi; Anwar, Muhammad (Jurnal Manajemen Pendidikan, 2025)
Improving the quality of learning in Vocational High Schools (Sekolah Menengah Kejuruan/SMK) is a strategic challenge in strengthening vocational education in Indonesia. The Center of Excellence Vocational School Program (SMK Pusat Keunggulan/SMK PK) has been introduced as a transformative initiative to enhance the relevance of vocational education to industry needs and technological development. However, the success of this program is not determined solely by technical and policy aspects, but also by the philosophical foundations that guide teaching and learning practices. This article aims to examine the relevance of educational philosophy in improving learning quality within the context of SMK Pusat Keunggulan. The study employs a literature review method with an analytical and reflective approach to educational philosophy and vocational education practices. The findings indicate that educational philosophy—particularly pragmatism, progressivism, and humanism—provides a normative and conceptual foundation for contextual, learner-centered, and competency-oriented learning. The integration of these philosophical perspectives supports meaningful learning experiences and contributes to the development of skilled, adaptive, and ethically grounded vocational graduates. Therefore, educational philosophy plays a crucial role in strengthening learning quality and ensuring the sustainability of the SMK Pusat Keunggulan program.